SYSTEMATIC REVIEW: KOMUNITAS WANITA LANSIA DAN FAKTOR RISIKO INKONTINENSIA URIN DI WILAYAH ASIA - Alya Shafira Hewiz; Novira Widajanti; Lukman Hakim; Rwahita Satyawati (LPPM Universitas BSI, 2022)
Knowledge of how the condition of elderly women in the community, especially in the Asian region, is interesting to know. Especially related to the study of risk factors and the relationship with urinary incontinence. This study aims to determine the risk factors and association with urinary incontinence in elderly women in particular in the Asian region. The method used is the PRISMA guidelines to be used as a systematic review. Sources of research data obtained from the data center. PubMed and Science Direct research in the period 2000-2020 with exclusion and inclusion criteria. Assessments are carried out for quality and risk using a standardized scoring system. Based on research in the Asian region, 3 articles were selected. Information obtained in communities in the Asian region in elderly women that the prevalence of urinary incontinence ranges from 19%–31.3%. Urinary incontinence is influenced by many factors, namely age, BMI, and smoking habits. The conclusion is that urinary incontinence is often experienced by elderly women in the Asian region and many factors can cause urinary incontinence. Awareness about urinary incontinence in elderly women can help better management.